A study of the records management practices of the University of the Philippines - Office of the Student Regent - Peoro, Rolly Francis (2007)
As an office mandated by the UP students, the UP Office of the Student Regent (OSR) is responsible for an effective and transparent representation of the whole UP student body. With the important role being played by the OSR, transactions are being done in fulfillment of its functions and subsequently records are created as evidence of these transactions. These records which are administrative, fiscal, legal value to the OSR are also historically significant to the history of student activism of the UP student body.